Oxidative potential of particulate matter at a German motorway. Issue 4 (19th March 2015) - Hellack, Bryan; Quass, Ulrich; Nickel, Carmen; Wick, Gabriele; Schins, Roel P. F.; Kuhlbusch, Thomas A. J.
Abstract : Ambient particulate matter (PM10) was sampled alongside a motorway at clear up- and downwind situations and analysed to their oxidative potential. Abstract : Ambient particulate matter (PM10) was sampled alongside a motorway in North-Rhine Westphalia, Germany, during a one-year period. In sum, 120 PM10 samples on quartz fibre filters, 60 samples at each side of the motorway, were taken during clear cross-wind direction situations, i.e. upwind (local background situation) and downwind (traffic influenced). To quantify the traffic-related oxidative potential (OP), or more precisely the hydroxyl radical (OH˙) generation potency, these samples were analysed to study their hydrogen peroxide dependent oxidant generation by Electron Paramagnetic Resonance (EPR) spectroscopy using the spin trap 5, 5-dimethyl-1-pyrroline- N -oxide. In addition the PM10 mass, the chemical composition and the NO x concentrations were determined. For PM10 mass and traffic tracers like Sb, Ba, elemental and organic carbon as well as for NO x, an additional contribution to the background concentration caused by the traffic was observed (factor: 1.3–6.0). The downwind measurements showed in 72% of cases higher OH˙ generation potencies with an average factor of 1.4. Significant correlations to OH˙ were detected for Fe ( r > 0.58) and Cu ( r > 0.57) for the upwind and overall (upwind + downwind, r > 0.44) dataset. At the downwind side these correlations were absent and are assumed to be covered by the interferences with additional soot particles leading to a quenching of OH˙. Accordingly, no significant overall correlation of the OH˙ generation potency with the traffic intensity was detected. The suggested quenching effect was confirmed via standard diesel soot (SRM 2975) measurements using the EPR approach. In summary, the traffic related PM causes an intrinsic OH˙ generation via Fenton-like reaction but obviously also leads to interferences and scavenging by traffic related carbonaceous compounds. In consequence, for future studies that would link the intrinsic OP and adverse health effects we suggest to analyse the relationship to EC/OC and to use in parallel also a further OP detection method.